2013
DOI: 10.1002/ar.22651
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Reveals Intersexual Differences in the Rat Brain Hippocampus

Abstract: It is widely accepted that intersexual differences occur in cognitive domains, e.g., in spatial learning and memory. The hippocampus plays important roles in the consolidation of information from short-term memory to long-term memory and spatial navigation. However, it still remains unknown whether the hippocampal proteomic profiling differs between males and females. In this study, we investigated the intersexual differences in protein expression of hippocampi using the two-dimensional electrophoresis analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Therefore, while estrous cycle stage did appear to impact both the dHPC proteome and phosphoproteome, the magnitude of this hormone-dependent impact was much greater on total versus phosphorylated protein levels. This is consistent with reports of significant estrous cycle-dependent fluctuations in protein and transcript levels within this brain region 43 , 44 , 52 54 and others such as the medial prefrontal cortex 55 .
Figure 4 Estrous cycle-dependent total and phosphoprotein expression in the dHPC.
…”
Section: Resultssupporting
confidence: 92%
“…Therefore, while estrous cycle stage did appear to impact both the dHPC proteome and phosphoproteome, the magnitude of this hormone-dependent impact was much greater on total versus phosphorylated protein levels. This is consistent with reports of significant estrous cycle-dependent fluctuations in protein and transcript levels within this brain region 43 , 44 , 52 54 and others such as the medial prefrontal cortex 55 .
Figure 4 Estrous cycle-dependent total and phosphoprotein expression in the dHPC.
…”
Section: Resultssupporting
confidence: 92%
“…Sex-dependent differences have been described in the neuronal structure, dendritic branching, as well as in the morphology and density of dendritic spines [2,29,42]. Sexrelated changes have been also investigated at the level of brain proteome [43][44][45][46]. Distler et al reported a profile of sex-specific synaptic proteins for different regions of the adult mouse brain, namely the hippocampus, cerebellum, prefrontal cortex, and striatum [43].…”
Section: Discussionmentioning
confidence: 99%
“…Distler et al reported a profile of sex-specific synaptic proteins for different regions of the adult mouse brain, namely the hippocampus, cerebellum, prefrontal cortex, and striatum [43]. It was also shown that the intersexual alterations in hippocampal protein expression pattern are related to those observed in behavioral tests [44]. Moreover, the differences in the proteomic profiling of the mouse hippocampus were shown to depend not only on the sex but also on the age of animals [45].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have previously demonstrated sex-specific differences in protein expression [39][40][41] . Similar to findings in brain, urine, and apheresis platelet supernatant, we observed a clear protein signature associated with sex for mouse plasma, in both KO and control mice.…”
Section: Sexual Dimorphismmentioning
confidence: 99%